2021
DOI: 10.1039/d1nj00207d
|View full text |Cite
|
Sign up to set email alerts
|

Triplet state (anti)aromaticity of some monoheterocyclic analogues of benzene, naphthalene and anthracene

Abstract: Aromaticity-antiaromaticity switch upon singlet-triplet transition of some biologically and synthetically important monoheterocycles (heteroatom = N, O, Si, P, S) derived from benzene, naphthalene and anthracene, was studied by employing energetic,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 118 publications
1
7
0
Order By: Relevance
“…Its triplet state energy is also close to the ideal value of ≥ 1 eV, [25] compared with 1.8 eV in the case of anthracene [24] . In our recent work, [26] we found that silicon substitution in benzene, naphthalene and anthracene most effectively reduced the S 0 −T 1 energy gaps, compared with heteroatoms such as nitrogen, phosphorus, oxygen and sulfur. This result was ascribed to the silicon atom‘s ability to quench the triplet state antiaromaticity of a hydrocarbon, whereas other heteroatoms retained or just reduced it.…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…Its triplet state energy is also close to the ideal value of ≥ 1 eV, [25] compared with 1.8 eV in the case of anthracene [24] . In our recent work, [26] we found that silicon substitution in benzene, naphthalene and anthracene most effectively reduced the S 0 −T 1 energy gaps, compared with heteroatoms such as nitrogen, phosphorus, oxygen and sulfur. This result was ascribed to the silicon atom‘s ability to quench the triplet state antiaromaticity of a hydrocarbon, whereas other heteroatoms retained or just reduced it.…”
Section: Introductionsupporting
confidence: 70%
“…Diatropicity of benzene in 1‐silanaphthalene appears to be larger. In our previous work, we showed that spin density localization decreases the extent of global antiaromaticity [26] . The AICD plots shown in Figures S6 and S7 also reveal diatropicity of benzene subunits in 1‐ and 2‐silanaphthalene, larger in the former, but weaker than in their ground states.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations